MECHANICAL VIBRATION CONTROL USING VARIABLE STIFFNESS ACTUATOR (Journal of Engineering, 2006)
Active control strategy had been used for controlling the vibration response, with considering thesimplification in the design and keep away from complexity and high cost in order to extend the actualapplication of the active control systems. The control program is responsible for identifying the acquireddata and make comparisons and decisions required for increase or decrease the actuator stiffness, byinstructing the control signal to open the inlet or the exhaust valve respectively. The PC sound card hasbeen used as a Data Acquisition Card. The proposed control strategy had been simulated and tested tocontrol the vibration response of a single degree of freedom spring-mass-damper system excitedharmonically at a fixed frequency and with variations of different system parameters (mass, dampingconstant, and excitation force). Two testing cases are used to investigate the ability of using the proposedactuator and the control strategy in the vibration control field.